OSMIUM ISOTOPIC COMPOSITIONS AND RE-OS CONCENTRATIONS IN SULFIDE GLOBULES FROM BASALTIC GLASSES - Roy-Barman M.; Chaussidon M.; Wasserburg G.J.; Papanastassiou D.A. (My University, 1998)
Sulfide globules present in basaltic glass were analyzed for Re and Os concentrations ([Re], [Os]) and 187Os/186Os from a selection of MORBs and Loihi lavas. The high Re and Os concentrations measured in sulfides confirm the chalcophile character of these elements. The partition coefficients of Re and Os between sulfide globules and silicate melt are estimated to be DRe=43 and DOs=4.8×104. The 187Os/186Os of the samples range from 1.054 to 1.387 for MORBs and from 1.091 to 1.146 for the Loihi samples. The low Re/Os ratios of sulfides make correction for in situ 187Re decay negligible. Several sulfide-rich (Os=500–1000 ppb) and sulfide-containing fractions from a Loihi sample gave essentially the same 187Os/186Os=1.095, demonstrating the possibility of obtaining very reliable data with our procedure. For some MORBs, shifts in 187Os/186Os for concentrates with low [Os] can be explained by the presence of Fe-oxyhydroxides enriched in Os by co-precipitation from seawater. The radiogenic 187Os/186Os ratios found in several sulfides with high [Os] cannot be explained by post-eruption contamination by Fe-oxyhydroxides or isotopic exchange between sulfides and seawater. We infer that some of the radiogenic 187Os/186Os ratios measured in MORB sulfides reflect the isotopic composition of the lava prior to eruption. Correlations were found between Os and B isotopic compositions and suggest that the radiogenic 187Os/186Os measured in MORBs are mainly due to assimilation of seawater-derived Os by the lavas during their ascent through the altered oceanic crust. MORBs with δ11B≤−10‰ seem to be suitable to study the 187Os/186Os ratio of the mantle. Considering only such `uncontaminated' samples, we still find a significant range of 187Os/186Os ratios (1.054–1.093) between two MORBs from the FAMOUS area. This result suggests that the mantle underlying the FAMOUS area is heterogeneous with regard to the Re–Os system and that it may have an Os signature distinct from that of abyssal peridotites collected on the Mid-Atlantic Ridge. Osmium isotopic ratios in Loihi lavas seem less sensitive to contamination than in MORBs. Two Os-rich Loihi basalts have similar isotopic ratios that apparently provide a good estimate of the 187Os/186Os ratio of the Loihi source (187Os/186Os=1.095±0.005).